Survey of Ontario Pharmacists' Knowledge, Resources and Barriers in Providing Perinatal Care - Abed, Aaya; Hung, Mae; Urslak, Randilynne; Landry, Christine; Boisvert, Audrey (Université d'Ottawa | University of Ottawa, 2026)
Background: Medication use during the perinatal period is challenging, as ethical concerns often exclude these patients from trials. With evolving perinatal care needs, clinicians continue to rely on limited evidence. Few Ontario pharmacists specialize in this area, highlighting gaps in knowledge, confidence and training. Objectives: To (1) explore Ontario pharmacists’ experience, knowledge, and practices in providing care during preconception, pregnancy, and breastfeeding; (2) identify the resources pharmacists use for reliable information on perinatal medication use; and (3) determine the barriers to pharmacy care for conceiving, pregnant, and breastfeeding patients. Methods: An electronic survey in English and French was sent to active Ontario pharmacists, collecting demographics, experience, self-assessed knowledge, resources, and barriers in caring for conceiving, pregnant, and breastfeeding patients. Data were analyzed anonymously using descriptive statistics in Excel. Results: While 92% completed training in the past year, 60% reported none in perinatal health, revealing educational gaps. Respondents reported infrequent patient counseling and lower confidence in preconception care. Main barriers included difficulty interpreting data (51%), limited resource awareness (39%), time constraints (37%), and lack of education (33%). Conclusions: Findings show significant gaps in pharmacists’ preparedness for perinatal care. Despite general education and continuing education, most lacked specific training and confidence in perinatal care. Enhanced perinatal medication training should be included in pharmacy education, with clear guidance on using specialized references to support consistent, evidence-based counseling and improve care quality.
Keywords: Perinatal; Medication; Ontario Pharmacists; Education; Medication Use Resources; Barriers